2009
DOI: 10.1021/op900252a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of an Antibacterial Compound Containing a 1,4-Substituted 1H-1,2,3-Triazole: A Scaleable Alternative to the “Click” Reaction

Abstract: The copper-catalyzed "click" reaction of an azide with an alkyne has become a popular method to build up 1,4-substituted 1H-1,2,3-triazoles in medicinal chemistry and this approach was used on a laboratory scale during the preparation of novel macrolide 1. However, the manufacture of the key azide component, as well as its subsequent use in the presence of a copper catalyst on a large scale, was associated with potential safety concerns. Therefore, a sequence was developed in which construction of the 1,4-subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(32 citation statements)
references
References 24 publications
0
29
0
3
Order By: Relevance
“…[9] In 1986, Sakai et al reported the synthesis of substituted 1,2,3-triazoles 11 through the reaction of an a,a-dichloroketone 10, tosylhydrazide and a primary amine (Figure 1 b). [10] The scope of this transformation was explored by Westermann and co-workers [11] and demonstrated on scale by Hanselmann et al, [12] providing a novel process to form this heterocyclic core. However, several limitations exist with this method.…”
mentioning
confidence: 99%
“…[9] In 1986, Sakai et al reported the synthesis of substituted 1,2,3-triazoles 11 through the reaction of an a,a-dichloroketone 10, tosylhydrazide and a primary amine (Figure 1 b). [10] The scope of this transformation was explored by Westermann and co-workers [11] and demonstrated on scale by Hanselmann et al, [12] providing a novel process to form this heterocyclic core. However, several limitations exist with this method.…”
mentioning
confidence: 99%
“…The scalability of this procedure was demonstrated by Hanselmann and co-workers, producing an antibacterial macrolide on a kilogram scale. 38 The proposed reaction mechanism starts by base-mediated formation of a vinyldiazine, which is followed by the addition of the amine substrate. After loss of HCl, generating an iminetosylhydrazone intermediate, a 1,5-H shift is most likely to take place providing the amino nucleophile for intramolecular cyclization.…”
Section: Other Nucleophiles/dipolarophilesmentioning
confidence: 99%
“…In contrast, 1,2,3‐triazoles are an important class of heterocycles, which have a wide spectrum of pharmaceutical applications. 1,2,3‐Triazole derivatives exhibit various biological activities such as antibacterial, antifungal, anticancer, antidiabetic potentials . Some of these derivatives have also shown significant inhibitory activity against α‐glucosidase .…”
Section: Introductionmentioning
confidence: 99%